PHYSICAL AND OPTICAL PROPERTIES OF THE FILMS ?i2Te3-Bi2Se3 (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Results of researches show, that film p-n the structures received by a method of discrete thermal evaporation in a uniform work cycle, are suitable for use in low-voltage devices.  As a result of work are received p-n heterojunctions in thin-film execution, described by high values of differential resistance. Show that, thermo endurance - T0 maybe using as characteristic of thermo endurance of optic materials. If heating flow, destruction temperature and internal surface temperature is measured during test, it is possible to determine value T0 and other necessity characteristics. As a result of the taking test was lead to comparison evaluation of considered materials. Working range of heating flow and up level heating embark have been determined.